Protective Effects of Urtica Dioica Extract on the Damage of Rat Small Intestinal Mucosa Caused by Diabetes - T Rezaei Aref (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Urtica is a dioecious plant, which has been introduced in Iranian traditional medicine as anti-diabetes. Since, the metabolic disorder caused by diabetes causes secondary pathophysiologic changes in multiple organs of the body, so the objective of this study was to investigate protective effects of Urtica Dioica extract on the small intestinal mucosa in addition to its anti diabetic effect. METHODS: In this experimental study, 14 male adult Wistar rats weighing 250-300 grams, in two groups (n=7) were used. First, the rats received an injection of streptozotocin (STZ) 50 mg/kg IV. The animals with fasting blood sugar more than 250 mg/dl were considered diabetic, one group of diabetic animals were treated with watery extract of Urtica dioica leaves (4 mg/kg daily IP injection) and other diabetic groups were considered as controls. After two months, the blood and intestinal tissue sample were taken and observed by histologist for the study of tissue parameters.FINDINGS: Blood sugar in treated group decreased from 400±52.2 mg/dl to 78.9±11.9 mg/dl (p<0.0004), whereas no change observed in diabetic group. In diabetic group, unlike the treated group necrosis and infiltration of mononuclear cells and damaged tissues were observed. Epithelium and lieberkuhn glands were destroyed, intestinal villa was shorted and atrophied, and also there were many cases of bleeding and exudates. CONCLUSION: The results of this study showed that urtica dioica has protective effect on small intestinal mucosa.